Spatial distribution of radioisotope concentrations in the offshore water and sediment of the Bay of Bengal (Indian Ocean), Bangladesh - Bhuiyan, Md. Khurshid Alam; Siddique, Mohammad Abdul Momin; Zafar, Mohammad; Mustafa Kamal, Abu Hena (Taylor & Francis, 2014)
Concentrations of natural and fall-out radionuclides in the offshore seawater and sediment from some parts of the Bay of Bengal, Bangladesh, were determined using a coaxial germanium detector. The average activities of 238U, 232Th, 40K and 137Cs were recorded as 31.2±5.8, 51.9±9.4, 686.4±170.5 and 0.5±0.6 Bq kg−1 dry weight, respectively, for sediment, and 4.8±1.2, 5.4±1.2 and 39.1±8.6 Bq L−1 for 238U, 232Th and 40K, respectively, in seawater. The concentration of 137Cs in seawater was below the detection limit. The concentration of sediment 238U was found to be positively correlated with 232Th (, p<0.05) and 40K (r=0.96, p<0.01), while 232Th was positively correlated with 40K (r=0.91, p<0.05). In sediment, the concentration of 238U was negatively correlated (r=−0.86, p<0.05) with sea depth. In the seawater sample, the only significant relationship found was between concentration of 232Th and water depth (r=−0.86, p<0.05). One-factor analysis of variance (ANOVA) showed that the level of radioisotope concentrations of seawater and sediment was highly significant for 238U (F=122, df=11, p=0.01), 232Th (F=143, df=11, p=0.01) and 40K (F=86, df=11, p=0.01). The results showed that the level of radioactivity decreased from coast to open sea. Imminent threat due to radioactivity was not observed in these parts of the Bay of Bengal.